Pengaruh Metode Audio Visual terhadap Pengetahuan Ibu Hamil tentang Pencegahan Ketuban Pecah Dini (KPD) - Audi Fatihah; Naura Assyifa Hayat; Yulidian Nurpratiwi; Meyke Rosdiana (STIKes YARSI Pontianak, 2025)
Background: Premature Rupture of Membranes (PROM) is an obstetric complication that poses a high risk of maternal and neonatal morbidity and mortality, primarily through infection, preterm labor, and impaired neonatal development. Prevention efforts can be implemented by improving pregnant women’s knowledge through health education. Objective: This study aimed to analyze the effect of audiovisual-based health education on improving pregnant women’s knowledge regarding PROM prevention. Methods: A pre-experimental one-group pretest–posttest design was employed. From a total population of 135 pregnant women recorded in the study area, 57 respondents were selected using accidental sampling. Data were collected using a structured questionnaire as the main research instrument. Results: The pretest assessment showed that 57.9% of respondents demonstrated good knowledge, whereas the posttest results revealed an increase to 93%. Statistical analysis yielded a p-value of 0.000 (<0.05), indicating a significant effect of audiovisual-based health education on pregnant women’s knowledge of PROM prevention. Conclusion: The audiovisual method is effective in improving pregnant women’s knowledge regarding PROM prevention and is recommended for integration into educational programs in primary healthcare facilities. These findings are expected to contribute to strengthening the quality of maternal nursing services, particularly in early detection and prevention of PROM among pregnant women.